Pengawasan Penyelenggaraan Parkir Tepi Jalan Umum di Kawasan Wisata Jalan Tunjungan pada Dinas Perhubungan Kota Surabaya - Lala Sevina Putri; Lukman Arif (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The large number of public roadside parking arrangements in the Jalan Tunjungan Surabaya Tourist Area that are not in accordance with existing regulations has caused a lot of anxiety among road users. This research aims to analyze how supervision is carried out by the Surabaya City Transportation Department in the implementation of public roadside parking to find out whether existing supervision makes public roadside parking comply with existing regulations, increases PAD resulting from parking fees, increases parking attendant compliance, as well as sanctions. given for existing violations. This research uses a qualitative descriptive approach with primary and secondary data sources. Data collection methods used were observation, interviews and documentation. Data analysis techniques use data collection, data condensation, data presentation, and drawing conclusions. This research uses the theory of implementation of supervision according to Soekidjo Notoatmodjo which consists of three, namely the object of supervision, the method of supervision, and the process of supervision. The results of this research indicate that supervision of the implementation of public roadside parking in the Jalan Tunjungan Tourist Area is not yet fully optimal because it does not meet the criteria in terms of supervision objects and supervision methods. This is due to the low level of discipline of parking attendants, in addition to the lack of socialization regarding parking management regulations to the public so that complaints are rarely made by the public. However, the criteria for the supervision process show that the process of carrying out supervision by the Surabaya City Transportation Service is in accordance with the established flow and the imposition of sanctions for violations by parking attendants is determined in accordance with applicable regulations. It is hoped that the results of this research can make supervision more optimal.